2003
DOI: 10.1074/jbc.m302457200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osteoclast Differentiation by Runx2 through Receptor Activator of Nuclear Factor-κB Ligand (RANKL) and Osteoprotegerin Regulation and Partial Rescue of Osteoclastogenesis in Runx2–/– Mice by RANKL Transgene

Abstract: Receptor activator of nuclear factor-B ligand (RANKL), osteoprotegerin (OPG), and macrophage-colony stimulating factor play essential roles in the regulation of osteoclastogenesis. Runx2-deficient (Runx2 ؊/؊ ) mice showed a complete lack of bone formation because of maturational arrest of osteoblasts and disturbed chondrocyte maturation. Further, osteoclasts were absent in these mice, in which OPG and macrophage-colony stimulating factor were normally expressed, but RANKL expression was severely diminished. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
111
3
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 58 publications
12
111
3
6
Order By: Relevance
“…As previously reported, osteoclasts were absent in Runx2 -/ -mice, due to diminished RANKL expression [19]. Besides, CA120-4 (a Runx2…”
Section: Figsupporting
confidence: 52%
See 2 more Smart Citations
“…As previously reported, osteoclasts were absent in Runx2 -/ -mice, due to diminished RANKL expression [19]. Besides, CA120-4 (a Runx2…”
Section: Figsupporting
confidence: 52%
“…However, adenoviral introduction of Runx2 into CA120-4 cells was able to induce RANKL expression while inhibit OPG expression to induce osteoclast differentiation [19]. These findings indicated that Runx2 promotes osteoclast differentiation by inducing RANKL and inhibiting OPG.…”
Section: Figmentioning
confidence: 64%
See 1 more Smart Citation
“…5 The effect of Runx2 function on osteoblast differentiation and OPG expression is controversial. [21][22][23] Some studies show that Runx2 induces RANKL expression and suppresses OPG expression, 24 and osteoblast differentiation was arrested in Runx2 overexpression cells. 22 Another study shows that Runx2 contributes to OPG activities.…”
mentioning
confidence: 99%
“…Metastatic breast cancer cells express bone sialoprotein, an important regulator of osteoblast differentiation under the control of RUNX2 and msh homeobox-2 (Msx2) transcription factors [137]. In normal bone marrow cells RUNX2 has been shown to promote osteoclast differentiation by inducing RANKL expression and suppressing OPG expression [138]. In MCF-7 and MDA-MB-231 breast cancer cell lines and prostate cancer cell lines RUNX2 transactivates expression of MMP-9, MMP-13 and VEGF indicating that RUNX2 contributes to the metastatic property of cancer cells [139].…”
Section: Cross Talk Between the Cancer Cell And The Bone Microenvironmentioning
confidence: 99%